Features of the use of “just in time” tools in the modern Russian economy - D. O. Melkozerova; N. Yu. Rud (E-Management, 2021)
One of the factors that ensure the company’s success in the market is a properly selected management system. This article is a study of the experience and prospects of implementing “just in time” and related modern management methodologies for Russian companies in a crisis situation caused by the СOVID-19 pandemic and its consequences. The authors suppose that there is a relationship between the use of these methods and a favorable socio-psychological climate in the team. The paper presents the theoretical material and experience ofcompanies belonging to various sectors ofthe economy. The study describes the conclusions based on the results of observation of the offi of the joint-stock company “Tochka”, which successfully applies “just in time”, scrum, agile, holacracy and lean thinking. The article describes the state of the company in the conditions of transition to remote work in connection with the COVID-19 pandemic.Based on the opinion of the employees obtained during the observation and conversation, the authors of the article suggest that the use of modern elements of the management philosophy allows the joint-stock company to maintain an optimal state of the socio-psychological climate, attracting employees, ensuring high productivity and engagement. Thus, the introduction of the just in time system and methods in modern Russian realities is quite feasible, but it will require signifiant effrts, fiancial investments, high-quality work on personnel selection.